Crystal structure of the spliceosomal DEAH‐box ATPase Prp2. Issue 7 (3rd July 2018) - Schmitt, Andreas; Hamann, Florian; Neumann, Piotr; Ficner, Ralf
Abstract : The DEAH‐box ATPase Prp2 is a key player during pre‐mRNA splicing. Here, the first four crystal structures of this spliceosomal factor are reported in two different states, and the flexibility of its C‐terminal domains and a previously undescribed ADP conformation are reported. Abstract : The DEAH‐box ATPase Prp2 plays a key role in the activation of the spliceosome as it promotes the transition from the B act to the catalytically active B* spliceosome. Here, four crystal structures of Prp2 are reported: one of the nucleotide‐free state and three different structures of the ADP‐bound state. The overall conformation of the helicase core, formed by two RecA‐like domains, does not differ significantly between the ADP‐bound and the nucleotide‐free states. However, intrinsic flexibility of Prp2 is observed, varying the position of the C‐terminal domains with respect to the RecA domains. Additionally, in one of the structures a unique ADP conformation is found which has not been observed in any other DEAH‐box, DEAD‐box or NS3/NPH‐II helicase.